Supercooling during crystallization of fusible metal particles in multilayer “carbon-metal-carbon” films - Petrushenko, S.I.; Dukarov, S.V.; Sukhov, V.N. (National Science Center "Kharkov Institute of Physics and Technology", 2016)
The results of studies of phase melting-crystallization transitions in thin films of fusible metals between thicker layers of amorphous carbon are given. It has been found that, due to poor wetting in contact systems under study, thin layers of fusible metals decompose into separate islands while first heated. Such films are a model of the system “fusible particles in the refractory matrix”. Using two independent in situ techniques (electrical resistance measuring and electron-diffraction studies during heating and cooling) values of supercooling during crystallization of liquid phase nanoparticles in multilayer C-Bi-C, C-Pb-C, C-Sn-C films, equal to 115, 135 and 160 K, respectively have been obtained. - - - - - - - - - - - Приводятся результаты исследований фазовых переходов плавлениекристаллизация в тонких пленках легкоплавких металлов, находящихся между более толстыми слоями аморфного углерода. Установлено, что вследствие плохого смачивания в исследуемых контактных системах уже при первом нагреве тонкие слои легкоплавких металлов распадаются на отдельные островки. Такие пленки представляют собой модель системы «легкоплавкие частицы в тугоплавкой матрице». С помощью двух независимых in situ методик (измерения электросопротивления и электронографических исследований в процессе нагрева и охлаждения) получены величины переохлаждения при кристаллизации наночастиц жидкой фазы в многослойных пленках (C-Bi-C, C-Pb-C, C-Sn-C), равные 115, 135 и 160 K соответственно.
Переохлаждение при кристаллизации частиц легкоплавких металлов в многослойных пленках «углерод-металл-углерод»
Ссылка на статью на русском языке: Петрушенко С.И., Дукаров С.В., Сухов В.Н. Переохлаждение при кристаллизации частиц легкоплавких металлов в многослойных пленках «углерод-металл-углерод» // Вопросы атомной науки и техники. Серия: Физика радиационных повреждений и радиационное материаловедение №4(104), 2016. стр. 118-124
Keywords: supercooling; multilayer films; phase transitions; Research Subject Categories::NATURAL SCIENCES::Physics::Condensed matter physics::Surfaces and interfaces